Rethinking Prostitution:Sociological Perspectives and Legal Practicesin India - Hajowary, Manasi; Goyary, Sanchuma (International Journal of Psychosocial Rehabilitation, 2019)
Prostitution as an institution can only be understood by exploring the economic and ideological base on which it rests. In the last few decades not only has the phenomenon reached alarming proportions but the forms of operation have changed as well. Governments all over the world have used the instrument of law as a means to deal with prostitutes and prostitution. Where, complex combinations of law, policy, and enforcement practices determine sex workers vulnerability to HIV and rights abuses. We identify “lack of recognition as a person before the law” as an important but undocumented barrier to accessing services and conclude that multi-faceted, setting-specific reform is neededrather than a singular focus on decriminalizationif the health and human rights of sex workers are to be realized.This paper attempts to examine the issues and legal protections underpinnings of the laws and their operation and how they affect sex workers in India.